2020
DOI: 10.3390/ijerph17082895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Healthy Children, Healthy Families, Healthy Communities Program for Obesity Prevention among Vulnerable Children: A Cluster-Randomized Controlled Trial

Abstract: Background: We aimed to examine whether the Healthy Children, Healthy Families, and Healthy Communities Program, consisting of multi-level strategies for obesity prevention tailoring the context of socioeconomically vulnerable children based on an ecological perspective, would be effective on improving their healthy lifestyle behaviors and obesity status. Methods: Participants were 104 children (and 59 parents) enrolled in public welfare systems in Seoul, South Korea. Based on a cluster-randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Physical activity was measured as the average number of days that children engaged in indoor or outdoor activities for at least 30 minutes daily. The recommendation level for sedentary behavior is defined as limiting screen time to less than 2 hours per day on weekdays; children were categorized as meeting this recommendation (coded as "1") or not meeting it (coded as "0") [22].…”
Section: ) Children's Health Behaviorsmentioning
confidence: 99%
“…Physical activity was measured as the average number of days that children engaged in indoor or outdoor activities for at least 30 minutes daily. The recommendation level for sedentary behavior is defined as limiting screen time to less than 2 hours per day on weekdays; children were categorized as meeting this recommendation (coded as "1") or not meeting it (coded as "0") [22].…”
Section: ) Children's Health Behaviorsmentioning
confidence: 99%
“…After full‐text screening, an additional 37 studies were identified. These included 20 studies 5,70–88 reporting 12 additional interventions and 17 studies 89–105 reporting outcomes from the interventions included in the review by Karacabeyli et al but those published after July 2017. The search of the clinical trial registries, the gray literature, and reference lists of included studies identified an additional 32 studies for inclusion in our review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…3 articles were included from Asia: 1 from Israel (24) , 1 from China (25) and 1 from South Korea (26) . We did not obtain any publication from Portugal.…”
Section: Resultsmentioning
confidence: 99%